Evaluasi Sebaran Rayap Di Perkebunan Kelapa Sawit Pada Jenis Tanah Yang Berbeda - Sudarmanto, Dandi; Santi, Idum Satia; Tarmaja, Samsuri (Program Studi Agroteknologi INSTIPER, 2024)
Termites are one of the pests in oil palm plantations that can cause physical damage to oil palm plants. This study aims to determine the type and colony of termites in mineral, peat and sandy soils and the effectiveness of their control. This research was conducted at PT. Binasawit Abadipratama located in Danau Seluluk District, Seruyan Regency, Central Kalimantan Province, Tangar Estate from March to April 2023. The research was conducted using a comparative method by comparing termite colonies in mineral soil, peat and with parameters in the form of termite species and the level of attack expressed by scoring, as well as secondary data in the form of termite nest census data in the garden archive to determine the effectiveness of control. The results showed that the largest termite colony was found in mineral soil. Termite species found in all soil types was Macrotermes gilvus, and no indication of termite infestation in oil palm trees. Based on the census data for the past three years, it can be concluded that the control that has been carried out is effective in reducing the termite colony from year to year.